Ngoko and Krama in Non Formal Diglosia Situation in Lamongan (A Sociolinguistic Study) - Rinzat Iriyansah, Muhamad (Jurnal KATA, 2019)
This research aims to observe a linguistic phenomenon in using “ngoko” and “kromo” as speech varieties in informal diglosioa situation of neighborhood domain in Lamongan. Descriptive qualitative method with content analysis teachnique is applied in this research. Non-participant observation with tapping technique was applied in data collection and the researcher also used participant observation with recording technique in some situations. The result shows that the diglossia situation among the speakers of Javanese speech community in Lamongan dominantly occurs in symmetrical and asymmetrical familiar situation. In a familiar symmetrical situation, all language varieties used is ngoko lugu-ngoko lugu. It indicates that the paralell social factor and close relationship among speakers cause the use of ngoko variety with specific variant of ngoko lugu. On the other hand, the familiar asymmetrical situation is dominated by the use of  ngoko lugu-ngoko lugu variety and the rest are varieties of ngoko alus-ngoko alus and ngoko alus-ngoko lugu as well as the T variety which is krama lugu-krama lugu.